Reduced autobiographical memory specificity, avoidance, and repression - Hermans, D; Raes, F; Iberico, C; Williams, J (2006)
Recent empirical work indicates that reduced autobiographical memory specificity can act as an avoidant processing style. By truncating the memory search before specific elements of traumatic memories are accessed, one can ward off the affective impact of negative reminiscences. This avoidant processing style can be viewed as an instance of what Erdelyi describes as the "subtractive" class of repressive processes.